Clinical performance of resin-bonded composite strip crowns in primary incisors: a retrospective study - D. RAM & A. B. FUKS (IAPD and Blackwell, 2006)
Full coronal restoration of carious primary incisors is indicated when: (1) caries is present on multiple surfaces; (2) the incisal edge is involved; (3) there is extensive cervical decalcification; (4) pulpal therapy is indicated; (5) caries may be minor, but oral hygiene is very poor (high-risk patients); or (6) the child’s disruptive behaviour makes placing Class III restorations difficult [1].